Cecal Volvulus: Etiology uncommon of intestinal occlusion acute - A Elbakouri; A Elwassi; Y Eddaoudi; M Bouali; K El Hattabi; FZ Bensardi; A Fadil (Archives of Clinical Gastroenterology - Peertechz Publications, 2022)
Caecum volvulus is, in frequency, the second part of the colon concerned by volvulus after the sigmoid and before the transverse colon. This pathology occurs in the cecum with abnormal mobility The mechanism of volvulus can be summarized in 2 either by torsion or tilting. The clinical picture is that of an acute intestinal occlusion by strangulation. The abdomen without preparation (ASP) and the abdominal CT are the radiological examinations of the first choice for the diagnosis. It is a surgical emergency, the conduct of which is to make a resection of the cecum and the terminal ileum. We report the case of a cecal volvulus admitted to the emergency room with an acute intestinal obstruction, the diagnosis was confirmed by an abdominopelvic CT scan and the treatment consisted of an ileocecal resection with immediate restoration of continuity, the postoperative follow-up was simple.